Ion polarisation-assisted hydrogen-bonded ferroelectrics in liquid crystalline domains. Issue 40 (28th September 2021) - Yuan, Guohao; Kimura, Yuko; Kobayashi, Takayuki; Takeda, Takashi; Hoshino, Norihisa; Akutagawa, Tomoyuki
Abstract : An alkylamide-substituted (−NHCOC10 H21 ) hydrogen-bonded dibenzo[18]crown-6 derivative (1 ) was prepared to stabilise the ionic channel structure in a discotic hexagonal columnar (Colh ) liquid crystal. Abstract : An alkylamide-substituted (−NHCOC10 H21 ) hydrogen-bonded dibenzo[18]crown-6 derivative (1 ) was prepared to stabilise the ionic channel structure in a discotic hexagonal columnar (Colh ) liquid crystal. The introduction of simple M + X − salts such as Na + PF6 − and K + I − into the ionic channel of 1 enhanced the ionic conductivity of the Colh phase of the M + ·(1 )·X − salts, with the highest ionic conductivity reaching ∼10 −6 S cm −1 for K + ·(1 )·I − and Na + ·(1 )·PF6 − at 460 K, which was approximately 5 orders of magnitude higher than that of 1 . The introduction of non-ferroelectric 1 into the ferroelectric N, N ′, N ′′-tri(tetradecyl)-1, 3, 5-benzenetricarboxamide (3BC ) elicited a ferroelectric response from the mixed Colh phase of (3BC ) x (1 )1− x with x = 0.9 and 0.8. The further doping of M + X − into the ferroelectric Colh phase of (3BC )0.9 (1 )0.1 enhanced the ferroelectric polarisation assisted by ion displacement in the half-filled ionic channel for the vacant dibenzo[18]crown-6 of (3BC )0.9 [(M + )0.5 ·(1 )·(X − )0.5 ]0.1 .